Electronic and Magnetic Properties of Some Topological Materials - Pal, Debarati (IIT(BHU) Varanasi, 2022)
Abstract is available in content.
This Thesis is submitted by Debarati Pal Ph.D.. Scholar IIT(BHU) Varanasi
Keywords: Electronic; Magnetic; Properties; Materials